Implications for restaging in gastric cancer with peritoneal metastasis based on the 15th Japanese Classification of Gastric Carcinoma: An analysis from a comprehensive center. Issue 7 (July 2020) - Wang, Jia-Bin; Liu, Zhi-Yu; Huang, Xiao-Bo; Chen, Qi-Yue; Zhong, Qing; Li, Ping; Lin, Jian-Xian; Lu, Jun; Cao, Long-Long; Lin, Mi; Tu, Ru-Hong; Huang, Ze-Ning; et al.
Abstract: Background: and purpose: For gastric cancer patients with peritoneal metastasis (GCPM), there is no universally accepted prognostic staging system. This study aimed to validate the predictive ability of the 15th peritoneal metastasis staging system (P1abc) of the Japanese Classification of Gastric Carcinoma (JCGC). Methods: The data of 309 GCPM patients from July 2007 to July 2017 were retrospectively analyzed. This study compared the prognosis prediction performances of P1abc, the previous JCGC PM staging (P123) and Gilly staging systems. Results: The survival curve revealed a significant difference in overall survival (OS) predicted by P1abc, P123 and Gilly staging (all P < 0.05), and the survival of the two adjacent substages were well distinguished by P1abc but not by P123 and Gilly staging. Both P123 and Gilly staging were substituted with P1abc staging in a 2-step multivariate analysis. The results showed that P1abc staging was superior to both P123 and Gilly staging in its discriminatory ability (C-index), predictive accuracy (AIC) and predictive homogeneity (likelihood ratio chi-square). A stratified analysis by different therapies indicated that for the P1a and P1b patients, OS following palliative resection combined with palliative chemotherapy (PRCPC) was better than that after palliative resection (PR) or palliative chemotherapy (PC) alone (P < 0.05). For the P1c patients, OS after receiving PC was significantly superior to that after receiving PRCPC or PR (P = 0.021). Conclusion: P1abc staging is superior to P123 and Gilly staging in predicting the survival of GCPM patients. Surgeons can provide these patients with appropriate treatment options according to the corresponding substages within P1abc.